A Burke–Schumann analysis of diffusion-flame structures supported by a burning droplet. Issue 4 (4th July 2017) - Nayagam, Vedha; Dietrich, Daniel L.; Williams, Forman A.
Abstract : A Burke–Schumann description of three different regimes of combustion of a fuel droplet in an oxidising atmosphere, namely the premixed-flame regime, the partial-burning regime and the diffusion-flame regime, is presented by treating the fuel and oxygen leakage fractions through the flame as known parameters. The analysis shows that the burning-rate constant, the flame-standoff ratio, and the flame temperature in these regimes can be obtained from the classical droplet-burning results by suitable definitions of an effective ambient oxygen mass fraction and an effective fuel concentration in the droplet interior. The results show that increasing oxygen leakage alone through the flame lowers both the droplet burning rate and the flame temperature, whereas leakage of fuel alone leaves the burning rate unaffected while reducing the flame temperature and moving the flame closer to the droplet surface. Solutions for the partial-burning regime are shown to exist only for a limited range of fuel and oxygen leakage fractions.